2000
DOI: 10.1242/dev.127.16.3407
|View full text |Cite
|
Sign up to set email alerts
|

Axis-inducing activities and cell fates of the zebrafish organizer

Abstract: We have investigated axis-inducing activities and cellular fates of the zebrafish organizer using a new method of transplantation that allows the transfer of both deep and superficial organizer tissues. Previous studies have demonstrated that the zebrafish embryonic shield possesses classically defined dorsal organizer activity. When we remove the morphologically defined embryonic shield, embryos recover and are completely normal by 24 hours post-fertilization. We find that removal of the morphological shield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Organizer size. The system is robust with respect to the change of the organizer size, which is consistent with the biological experiments [7]. In our simulations, we assume that the organizer is located at the right end, just as the wild type case [13].…”
Section: Ii) General Solution Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Organizer size. The system is robust with respect to the change of the organizer size, which is consistent with the biological experiments [7]. In our simulations, we assume that the organizer is located at the right end, just as the wild type case [13].…”
Section: Ii) General Solution Analysissupporting
confidence: 84%
“…In [13], a nonlinear reaction-diffusion model on both three-dimensional and a simplified one-dimensional spatial domains was developed for computational analysis of BMP morphogen gradient formation in dorsal-ventral patterning of the zebrafish embryo. The model predicts that the dorsal organizer of the zebrafish embryo plays a key role in forming a stable non-homogeneous morphogen gradient, and the prediction agrees well with the existing biological experiments [7]. We briefly describe the model in the following paragraphs.…”
supporting
confidence: 78%
“…The involvement of N-cadherin in the notochord formation may also depend on the surrounding tissues because interactions between the notochord and surrounding tissues in uence their development (Placzek, 1995;Saude et al, 2000). For example, the neural tube and the notochord are known to in uence each other's development (Corallo et al, 2015;Stemple, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The anteroposteriorly elongated, rigid, and yet exible notochord is composed of cells cohered in a tandem fashion as rod-shaped tissue; it supports embryos' structural integrity and locomotion (Corallo et al, 2015;Stemple, 2005). In addition, the notochord is an organizer that secretes signals to orchestrate the development of many surrounding tissues (Placzek, 1995;Saude et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Waddington discovered that secondary tissues could also be induced by transplanting the primitive node of donor duck embryos to the epiblast of the host chick embryo ( Waddington, 1933 ; Waddington and Schmidt, 1933 ). About 60 years later, scientists Koshida S and Saude L found that the chicken Hensen’s node and the zebrafish shield induced formation of a secondary axes in zebrafish embryos ( Koshida et al, 1998 ; Saude et al, 2000 ). Contemporary, developmental biologists showed that transplanting the mouse node of a 7-days mouse embryo to the posterolateral side of the host also induced formation of a secondary axis ( Varlet et al, 1997 ; Koshida et al, 1998 ; Joubin and Stern, 1999 ).…”
Section: Introductionmentioning
confidence: 99%